PHATIC COMMUNION AS A UNIFIER AS PORTRAYED IN ‘WONDER’ - Sakinah Mawadda (Universitas Sebelas Maret, 2021)
Phatic communication or so called ‘phatic communion’ is said to be a kind of language used to create, to maintain and to strengthen the social bond between individuals. However, the concept of phatic communication in which it requires neither an exchange of information nor a specific purpose in its use raises the question regarding the necessity and the effectiveness of phatic communication. Responding to this issue, this study is conducted to show the significance of phatic communication in colloquial speech event. This study aims to prove the role of phatic communication as a unifier between individuals as portrayed in Wonder movie reflected in the life of a boy with Treacher Collins syndrome, Auggie. Considering the hardships he encounters in his social life, this study aims to see how phatic communication acts as a unifier for Auggie by scrutinizing the types and the functions of phatic communication in his social life. The analysis suggests that 1) the types of expressions serving as phatic communication in Wonder are divided into greeting, making small talk, agreeing on something and joking, and 2) the functions of the phatic expressions are to express solidarity and friendship and to create harmony and comfort.Keywords: Phatic Communication, Phatic Communion, Unifier